Homogeneity and Heterogeneity in the Results of Two Public Policy Evaluation Instruments - de Camargo Lima, Rodolfo; Rebolledo Toro, Edgar (Revista del CLAD Reforma y Democracia, 2020)
The evaluation of public policies is a fundamental stage of transparency and accountability within the public policy cycle. This paper analyzes the behavior of two Chilean civil service evaluation instruments of management and public policy in the recent decades: the Management Improvement Program (PMG) and the Evaluation of Government Programs (EPG). Data from official reports and information available on the website of the Budget Office (DIPRES) were used for this purpose. The research uses temporal and descriptive statistics to show its results. The PMG instruments showed a concentrated and homogeneous pattern in the last 16 years, with a temporary average percentage of achievement by ministry that is positioned above 95%. On the other hand, the EPG presented a diffuse and heterogeneous pattern in the last two decades, with high oscillation, but with a time average between low and medium quality in the evaluated public policy programs.
Keywords: Evaluation; Policies Evaluation; Programs Evaluation; Public Policy; Administrative Indicators; Case Analysis; Chile